Juego de palabras : los discuros presidenciales sobre el crimen - Fondevila, Gustavo (El Colegio de México, 2013)
The democratization process in México has been exhaustively studied, although little has been discussed on the effect it has had on the official conception on public safety and crime control. This document poses a research question pointing out to an aspect on the subject: the presidential discourses. Which was the “discursive” change on the governmental conception of public safety and crime control on the sexennial transition of Ernesto Zedillo and Vicente Fox?